Penerapan Metode Blended Learning dalam Pembelajaran pada Masa Pandemi Covid-19 - Siti Muslikhah; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
This study aims to analyze learning innovation, blended learning model as a strategy in learning during the covid 19 pandemi. This research method uses a literature review of journals. The analysis of this study concludes that blended learning is needed to improve the quality and quantity of learning. This learning model combines face-to-face and online learning approaches. With a mixed learning strategy, learning becomes flexible. The blended learning model can make it easier for participants to access learning materials and materials, increase learning motivation and participants' independence so that learning is more effective. This blended learning model can be applied as a learning model in educational institutions. To improve the quality of blended learning in learning, it is necessary to have adequate information technology infrastructure and student independence.